Bleeding Risk and Mortality Associated With Uninterrupted Antithrombotic Therapy During Percutaneous Endoscopic Gastrostomy Tube Placement. (23rd September 2021) - Thosani, Nirav; Rashtak, Shahrooz; Kannadath, Bijun Sai; Munjal, Akhil; Meriwether, Matthew; Yoon, Eric D.; Hermann, Andrew; Ali, Sara; Haddad, Paul G.; Patil, Prithvi; Ramireddy, Srinivas; Badillo, Ricardo; et al.
Abstract : INTRODUCTION: Antithrombotic therapy is often interrupted before the placement of a percutaneous endoscopic gastrostomy (PEG) tube because of potentially increased risk of hemorrhagic events. The aim of our study was to evaluate the risk of bleeding events and overall complication rates after PEG in patients on uninterrupted antiplatelet and anticoagulation therapy in a high-volume center. METHODS: Data regarding demographics, diagnoses, comorbidities, and clinical outcomes pertinent to PEG were collected from 2010 to 2016. Furthermore, data regarding antithrombotic therapy along with the rate of minor or major complications including bleeding associated with this procedure were analyzed. Significant bleeding was defined as postprocedure bleeding from PEG site requiring a blood transfusion and/or surgical/endoscopic intervention. RESULTS: We included 1, 613 consecutive PEG procedures in this study, of which 1, 540 patients (95.5%) received some form of uninterrupted antithrombotic therapy. Of those patients, 535 (34.7%) were on aspirin, 256 (16.6%) on clopidogrel, and 119 (7.7%) on both aspirin and clopidogrel. Subcutaneous heparin was uninterrupted in 980 (63.6%), intravenous heparin in 34 (2.1%), warfarin in 168 (10.9%), and direct-acting oral anticoagulation in 82 (5.3%) patients who overlapped on multiple drugs. We observed 6 significant bleeding events in the entire cohort (0.39%), and all were in subcutaneous heparin groups either alone or in combination with aspirin. No clinically significant bleeding was noted in patients on uninterrupted aspirin, warfarin, clopidogrel, or direct-acting oral anticoagulation groups. Only 5 patients (0.31%) had PEG-related mortality. DISCUSSION: The risk of significant bleeding associated with the PEG placement was minimal in patients on uninterrupted periprocedural antithrombotic therapy.